THE EXISTENCE AND ROLE OF LEGAL HIGHER EDUCATION IN LAW ENFORCEMENT DURING THE COVID-19 PANDEMIC IN INDONESIA - Moch Thariq Shadiqin; Ummi A'zizah Zahroh (Jurnal PPI Dunia, 2022)
The Covid-19 pandemic has made learning in Higher Education carried out at home. This is a challenge in itself for the Higher Education Law, how it can still produce excellent and professional law enforcement human resources even though they are limited. This article aims to see Law Higher Education try to continue to show its existence and role. The type of research in this article is normative juridical law research. The data collection method used in writing scientific papers is carried out using library research, namely by searching for legal materials and social data relevant to the subject matter, which is the study in writing this scientific paper. Law Higher Education made a breakthrough in the form of learning through Microsoft Teams and Zoom applications. Not only that, this official institution tries to continue to hold activities outside of lectures, such as workshops, webinars using the Youtube channel. It's to continue to produce professional law graduates. However, it is undeniable that there are still several obstacles, including mastery of technology, the risk of casualties, and the opportunity to study practical work, which can only be done in student domiciles.